La pregunta por la pregunta - Camino Macedo, Federico (2022)
With Heidegger, the detailed study of what it is and what questioning implies begins in the history of philosophy, since, with the exceptions of Plato and Aristotle and possibly Descartes, a question as such was neglected, despite the fact that it is in the field of philosophy that questioning achieves its maximum fulfillment. The reflections of this article study the links between Érōs and the question (erṓtēsis), an essential connection that, although it is not etymo-logical but phonetical, allows us to find the common amphibian structure that joins together these two dimensions and makes it possible to establish an essen-tial link between Érōs as the strength and the question as the place where that strength is expressed, what is nothing other than philosophy as love or aspiration to knowledge.In the question-answer unit is that knowledge as a unit of what is sought and what is found.The question, a kind of symbol that links together, supposes a distancing that eliminates the immediacy of what is given and establishes a distance in which what is questioned and its aspiration to the unity of knowledge are placed. The question is the piety of thought, as Heidegger says, and the philosophical ques-tions, the expression of our first and last perplexities.